2021
DOI: 10.1002/iid3.467
|View full text |Cite
|
Sign up to set email alerts
|

Long‐coronavirus disease among people living with HIV in western India: An observational study

Abstract: Background Long‐COVID is emerging as a significant problem among individuals who recovered from COVID‐19. Scant information is available on the prevalence, characteristics, and risk factors for long‐COVID among people living with HIV (PLHIV). Setting A tertiary level, private, HIV clinic in western India. Methods A prospective, observational study was conducted to assess the prevalence of long‐COVID among PLHIV. Long‐COVID was defined as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…There are limited data on PASC among PWH [55], however. One single-center study suggested that acute illness severity in PWH was significantly associated with PASC with 44% of participants experiencing at least one symptom 30 days after recovery [40], however it did not find an association between clinical parameters such as CD4+ T cell count, viral load, demographics or comorbidities and the presence of PASC, and did not compare PWH with HIV-negative individuals. Another retrospective study suggested that HIV was one factor that was associated with higher risk of PASC approximately one year after COVID-19 diagnosis among those requiring emergency department or hospital-based care [56], but the analysis was limited to 10 PWH and did not include biological measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited data on PASC among PWH [55], however. One single-center study suggested that acute illness severity in PWH was significantly associated with PASC with 44% of participants experiencing at least one symptom 30 days after recovery [40], however it did not find an association between clinical parameters such as CD4+ T cell count, viral load, demographics or comorbidities and the presence of PASC, and did not compare PWH with HIV-negative individuals. Another retrospective study suggested that HIV was one factor that was associated with higher risk of PASC approximately one year after COVID-19 diagnosis among those requiring emergency department or hospital-based care [56], but the analysis was limited to 10 PWH and did not include biological measurements.…”
Section: Discussionmentioning
confidence: 99%
“…While there are massive efforts underway to understand the prevalence and pathophysiology of PASC, there are limited data among PWH [30]. One single-center study suggested that acute illness severity in PWH was associated with PASC with 44% of participants experiencing at least one symptom 30 days after recovery [31], however it did not find an association with CD4+ T cell count, viral load, demographics or comorbidities, and did not compare PWH with HIV-negative individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…63 To the best of our knowledge, thus far only one study has investigated the risk of post-acute symptoms following COVID-19 and found that moderate to severe disease was associated with an increased risk of persistent symptoms in PWH. 95 …”
Section: Discussionmentioning
confidence: 99%
“…One small study characterized PASC in an Indian cohort of 94 PWH, finding a PASC prevalence of 43.6% and increased risk among persons who had had moderate-severe COVID-19 compared to mild disease. 40 There is an urgent need to more broadly characterize risk and manifestations of PASC, including the relationship between immunosuppression and incidence of PASC, in PWH in larger, more diverse global cohorts. This information is critical to guide post-COVID HIV care, to understand potential interactions between HIV and COVID, and to inform interventional strategies to prevent and treat PASC in PWH.…”
Section: Hivmentioning
confidence: 99%